Functional Testing of The Dana E-Wallet Transaction Features Using Black Box Testing - Neng Eva Masliah; Rifa Vida Zahrani; Khairunnisa Dwi Wahyuningtyas; Tiara Putri Latifani Dianata; Muhamad Aditya Suhendar; Muhamad Nabil Arrafi; Subhanjaya Angga Atmaja (SEAN Institute, 2025)
The rapid development of financial technology in Indonesia has driven the adoption of digital wallet applications such as DANA, which offers various digital transaction features. However, the high usage rate is not always accompanied by guaranteed functional reliability of the application. This study aims to test the functionality of transaction features in the DANA application through a quantitative approach using the black box testing method. The research design is descriptive quantitative, utilizing 20 test scenarios developed based on Equivalence Partitioning (EP) and Boundary Value Analysis (BVA) techniques, with sampled transaction features including login, PIN verification, money transfer, adding a bank account, and requesting money. The analysis technique involves calculating the number of valid and invalid scenarios based on the match between the actual output and the expected output. The results show that 14 out of 20 scenarios (70%) performed as expected, while the remaining six failed, with most failures found in the login and PIN verification features. These findings highlight weaknesses in the input validation system and insufficiently informative error notifications. This study makes an important contribution to the development of e-wallet applications, particularly in improving validation quality, authentication security, and the overall user experience.